2013
DOI: 10.1055/s-0032-1328429
|View full text |Cite
|
Sign up to set email alerts
|

Dioecy in Plants - Is It an Important Factor for Phytochemists to Consider?

Abstract: Plants with separate male and female flowers are termed dioecious. Dioecy is not rare, yet is a characteristic that could potentially impact the phytochemical and subsequent pharmacological properties of a species. This is a brief insight which highlights why the sex of the plant might be an important factor to consider for researchers within phytochemistry related fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Recent studies have succeeded in comparing the chemical composition between male and female plants, including the analysis of secondary metabolites and its fluctuation based on changes of the season [29] and sex related differences [30]. The obtained results also suggest that diterpene resin composition should give information about the variable sex in the dioecious tree A. chilensis.…”
Section: Percent Diterpene Composition and Collection Time (Month/seamentioning
confidence: 85%
“…Recent studies have succeeded in comparing the chemical composition between male and female plants, including the analysis of secondary metabolites and its fluctuation based on changes of the season [29] and sex related differences [30]. The obtained results also suggest that diterpene resin composition should give information about the variable sex in the dioecious tree A. chilensis.…”
Section: Percent Diterpene Composition and Collection Time (Month/seamentioning
confidence: 85%
“…exhibited a higher concentration of anthraquinones, phenolics and terpenoids respectively than those of females, which contrasts with the resource allocation theory (Banuelos et al, 2004;Massei et al, 2006). Hence it is evident that resource allocation might have a profound effect on the composition and concentration of secondary compounds between individuals of dioecious species (Simpson, 2013).…”
Section: Introductionmentioning
confidence: 80%
“…Resource allocation, including trade-offs between allocation to defense, growth and reproduction, is different between genders of dioecious plants (Obeso, 2002). Several studies have shown that differences in reproductive demands between the genders of dioecious plants cause gender physiology divergence that in turn affects the production and concentration of secondary metabolites (Bajpai et al, 2016;Milet-Pinheiro et al, 2015;Simpson, 2013). Herbivory has been suggested as a selective pressure that has resulted in the evolution of dioecy (Bawa, 1980), and studies have utilized the plant resource allocation theory (Levins, 1968) to understand the patterns of plant-herbivore interaction (Obeso, 2002), herbivore plant gender preferences (Hjalten, 1992), plant browsers (Danell et al, 1991), folivores (Maldonado-López et al, 2014), pollinators (Milet-Pinheiro et al, 2015), and gall formers (Wolfe, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Salix, there are male and female plants. It has been pointed out that the existence of sexually different forms could potentially impact the phytochemical and pharmacological properties of extracts and medical products derived from these plants (Simpson, 2013). A previous study by Reisch and Achenbach (1992a) has indeed shown that there are some differences in the production of furanocoumarins in the bark between male and female bushes of S. japonica.…”
Section: Conclusion Discussion and Future Perspectivesmentioning
confidence: 99%